Pengaruh Partisipasi Anggaran, Literasi Keuangan Dan Pemberdayaan Masyarakat Terhadap Kualitas Anggaran Pendapatan Dan Belanja Desa - Meylan Priska; Usup Riassy Christa; Fitria Husnatarina; Danes Jaya Negara; Roby Sambung; Achmad Syamsudin (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
Research in the field of management by strengthening financial literacy to strengthen the quality system of village income and expenditure budgets. Building a village with budget participation and community empowerment in the Gunung Mas district village apparatus in Palangka Raya Province. The research was conducted in seven sub-districts in Gunung Mas district, with 77 respondents being village officials. This type of quantitative research with the SPSS application shows that budget participation on the quality of APBdes is significant at 73%, then the results of financial literacy research are significant at 74%. The next result of community empowerment on the quality of APBdes is 59%. The implication of the results states that they can be used as a reference in improving the quality of APBdes and for further research to develop results with financial applications in village financial reports